A study of caesarean sections in referred cases - Shah, Devanshi; Patel, Arti; Mandaliya, Maitry (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Referral is a coordinated movement of healthcare seekers through the health system to reach a high level of care in a small and often fatal window of time. Even physiological processes like pregnancy and childbirth are not free of complications. The purpose of this study is to understand maternal and foetal outcome in caesarean sections in referred cases. Methods: A prospective study was carried out in the OBGY department of SMT.SCL HOSPITAL, NHL Municipal medical college from April 2020 to April 2021. All referred antenatal and intranatal patients to our tertiary care centre with >20 weeks of gestation who underwent caesarean section with referral note. Results: A total 64% patients were referred from community health center. 63.5% patients were referred due to lack of high-risk management services. 211 patients underwent caesarean section while 69 patients had normal vaginal delivery. Difficulty in delivery of the baby was encountered in 53% of cases due to deep engagement of the fetal head. Major cause of admission in NICU was sepsis (38.6%) followed by prematurity (23.8%). Conclusions: Cesarean section is one of the quickest and most efficient method in the delivery of the baby and thus should in considered in patients in critical situations .The millennium development goals defined by united nation includes one goal (MDG 5) towards improving maternal health which still remains a challenge. Thus, improving knowledge of women regarding good antenatal care and strengthening referral services will play a big role in this.